2019
DOI: 10.1002/aorn.12896
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Retinoblastoma and Enucleation in Pediatric Patients

Abstract: Retinoblastoma is a rare malignancy of the eye affecting children, most commonly four years old and younger. Although chemotherapy and radiation treatment aim to spare the eye, in some cases, enucleation (ie, removal of the eye) is required to prevent cancer metastases or recurrence. Enucleation procedures are primarily performed at specialty institutions and may involve the surgical placement of an implant in the orbit of the eye. Unique perioperative considerations are required because of the age of the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
8
0
7
Order By: Relevance
“…Canada reported that the average age of diagnosis of monocular onset is 27 months, the average age of diagnosis of binocular onset is 15 months, and the average age of diagnosis of single and double eyes in Kenya is 36 months and 25 months [1,3,6]. In our retrospective study, there were 20 males and 20 females, and RB onset within 5 years of age, with a median age of 15.5 months, which basically consistent with the literature reports [1,3,22]. RB cells are derived from susceptible vertebral photoreceptor cells of retinal precursors.…”
Section: Discussionsupporting
confidence: 89%
“…Canada reported that the average age of diagnosis of monocular onset is 27 months, the average age of diagnosis of binocular onset is 15 months, and the average age of diagnosis of single and double eyes in Kenya is 36 months and 25 months [1,3,6]. In our retrospective study, there were 20 males and 20 females, and RB onset within 5 years of age, with a median age of 15.5 months, which basically consistent with the literature reports [1,3,22]. RB cells are derived from susceptible vertebral photoreceptor cells of retinal precursors.…”
Section: Discussionsupporting
confidence: 89%
“…Although retinoblastoma is a rare malignancy of the eye, it is the most common intraocular malignancy in children and occurs most frequently in those aged 4 years or younger [34]. In this study, almost half of the tumors were retinoblastomas (48.3%), and the prevalence was highest in children aged 0 to 3 years.…”
Section: Table 4 Distribution Of Congenital Ophthalmic Diseases By Ag...mentioning
confidence: 51%
“…The priority goal of retinoblastoma management is to save the child's life; secondary goals are globe salvage and optimization of visual function [38]. Chemotherapy is a potential vision-keeping approach, but enucleation must be implemented promptly for advanced retinoblastoma [34]. Retinoblastoma is considered a curable malignant tumor with a near 100% survival rate if timely intervention is conducted during the early stage at initial presentation [39].…”
Section: Table 4 Distribution Of Congenital Ophthalmic Diseases By Ag...mentioning
confidence: 99%
“…Even today, this remains the treatment of choice for advanced retinoblastoma, recurrence or metastasis, especially if the tumours are unilateral or the affected eye has lost its function [23]. Enucleation has significant consequences at the visual, cosmetic, and psychological level as the child's mutilation can shelter feelings of anger and anxiety [24]. External Beam Radiotherapy (EBRT) was widely used as globe salvage therapy since its implementation in 1950 by Henry Kaplan.…”
Section: Accepted Articlementioning
confidence: 99%